Visi dan Paradigma Pendidikan Agama Islam (PAI): Kualitas, Integratif, dan Kompetitif - Rudi Ahmad Suryadi (Tarbiyah Departement collaboration with AMCA, 2016)
The implementation of Islamic Teaching (Pendidikan Agama Islam) relates with achieving the goal of faith, piety and best character based on the spirit of UU RI Nomor 20 of 2003 on National Education System. In achieving it’s quality in the context of national development paradigm requires an understanding it. Paradigm is a foundation in quality development strategies. The paradigm that leads to the achievement of quality, integrated, and competitive be the foundation and frame for the realization of strategic programs with various dimensions. Paradigm of Quality, Integrative, Competitive in Religious Character frame becomes viewpoint for future. Expectations of education that touches the ease of access and quality can always be realized with a variety of synergistic efforts of various dimensions.